Meningkatkan Kosakata Anak Melalui Metode VAKT (Visual, Audio, Kinestetik, Dan Taktil) Bagi Anak Tunagrahita - Sani, Rika Fatimah; Armaini, Armaini (Jurnal Penelitian Pendidikan Khusus, 2022)
This type of research is a type of classroom action research (CAR), with the aim of knowing how to increase the vocabulary of mentally retarded children through the VAKT method. This research was carried out in collaboration with class VIII teachers. All research activities are incorporated into several processes, namely planning, observation and reflection. The study was conducted on mild mentally retarded children for class VIII SLB N Padangsidimpuan with two children with initials S and RA who have low levels of vocabulary skills. The study was divided into two cycles in which each cycle had four stages and 4 meetings in each cycle. From the results of the study, it was obtained that the increase in vocabulary with the initial ability of S children got a less value, namely 31%, after the first cycle they got 38% in the second cycle they got 83%. After that, the initial ability of RA children got a value of 36%, after the first cycle it got a value of 53%, and in the second cycle it got 83%. It can be concluded that the VAKT method can improve the ability to recognize children's letters.